Peran Otoritas Jasa Keuangan (OJK) dalam Pasar Uang dan Modal di Era Digital - Mochammad Su’eb; Yonika Nazla Rohma (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The digital era has brought significant transformation in the financial sector, including the money market and capital market in Indonesia. Innovation in financial technology (fintech), digitalization of services, and increasing volume of online transactions require adaptive and responsive supervision from the authority institution. This study aims to analyze the role of the Financial Services Authority (OJK) in regulating, supervising, and developing the money market and capital market amidst the development of digital technology. The research method used is qualitative with a descriptive-analytical approach through literature studies and secondary data from official OJK reports and related regulations. The results of the study show that OJK plays a central role in maintaining the stability and integrity of the financial market through strengthening digital regulations, technology-based supervision (suptech), and investor protection. In addition, OJK also encourages digital financial inclusion and literacy to create a healthy and sustainable market ecosystem. These findings emphasize the importance of policy adaptation and strengthening OJK's institutional capacity in facing challenges and opportunities in the digital era.